SOCIAL CONSTRUCTIVISM AS A SOLUTION TO RATIONALITY IN POSTNONCLASSICAL EPISTEMOLOGY - O. V. Molokova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose. In this article the epistemology is investigated in such direction of social thought as social constructivism. The occurrence and popularity of a socially-constructivist paradigm was preceded by polemic between defenders of orientation of a science on the objectivity, positions adhering positivistically- universalistic and their opponents defending positions relativism. In the centre of discussion of scientific community there were such important problems for philosophy, as search for scientific true; objectivity of scientific knowledge and a relative autonomy of a science; relativization scientific knowledge. Methodology. Features of modern constructivism − in a special sight at knowledge, in a new foreshortening of its consideration when it represents itself as the tool of maintenance of ability to live of an organism as integrity (the individual, social group, a society). The outstanding characteristics of constructivism are the new foreshortening of consideration of possibilities of social knowledge − as constituting element of human experience of an everyday life. Scientific novelty. The important point is studying of how the scientific knowledge influences life of people, changes and structures life of the person. As the knowledge does not correspond any more with the objective world by a reflexion principle, loses sense and a question on its conformity of a reality that removes stubborn problems of true, reliability, objectivity. Conclusions. Social constructivism creates new possibilities for studying a problem of true and connected with it epistemological procedures of understanding, an explanation, interpretation, allows to look at the nature of human knowledge differently. In modern scientific researches the wide circulation is received by idea of designed character social and cultural the validity. This idea is supported with conclusions of variety of interdisciplinary approaches (the general theory of systems, the self-organising theory etc.) which form more difficult models of a reality and culture. The further development of the given direction of knowledge opens prospects for various kinds of humanitarian activity.